An empirical assessment of business cycle asymmetries: evidence from Malaysia - Abdul Manap, Turkhan Ali (2009)
Asymmetry is a key feature to understand the different behavior of expansions and recessions, and it provides a stylized fact that business cycle models should help to explain. This paper intends adopt Clements and Krolzig (2003) parametric tests to determine the asymmetric properties of business cycle fluctuations of Malaysia for the period from 1980Q1 to 2006Q4. In particular, we model the business cycles of Malaysia with the help of Markov Switching models and then apply the recently proposed parametric tests by Clements and Krolzig (2003) to test for three types of asymmetry of business cycle: steepness, deepness and sharpness.